Basic FGF mediates an immediate response of articular cartilage to mechanical injury. - Vincent, T; Hermansson, M; Bolton, M; Wait, R; Saklatvala, J (2002)
The extracellularly regulated kinase (ERK), one of the three types of mitogen-activated kinases, was rapidly activated after cutting porcine articular cartilage either when maintained as explants or in situ. Cutting released a soluble ERK-activating factor from the cartilage, which was purified and identified by MS as basic fibroblast growth factor (bFGF). Experiments with neutralizing Abs to bFGF and an FGFR1 tyrosine kinase inhibitor showed that this growth factor was the major ERK-activating factor released after injury. Treating cartilage with the heparin-degrading enzyme heparitinase also caused release of bFGF, suggesting the presence of an extracellular store that is sequestered in the matrix and released upon damage. Basic FGF induced the synthesis of a number of chondrocyte proteins including matrix metalloproteinases 1 and 3, tissue inhibitor of metalloproteinases-1, and glycoprotein 38, which were identified by MS. The strong induction of matrix metalloproteinases and tissue inhibitor of metalloproteinases-1 suggests that bFGF could have a role in remodeling damaged tissue.